(untitled) (Qawanin Jurnal Ilmu Hukum, 2024)
The purpose of writing this thesis is to analyze the nature of village conflict in terms of the form of guaranteeing the traditional origin rights of village communities since the issuance of Law No. 6 of 2014 concerning Villages. The aim of writing this thesis is to analyze the nature of village conflict in terms of the form of guaranteeing the traditional origin rights of village communities since the issuance of Law No. 6 of 2014 concerning villages. This research method uses normative research. The types and sources of legal materials used in preparing this research are primary legal materials originating from statutory regulations, secondary legal materials obtained from collecting library data in the form of literature, scientific works, journals, documentation. from various related institutions or agencies, tertiary legal materials, guidance on primary and secondary legal materials in the form of encyclopedia dictionaries, materials from the internet and scientific literature, and data collected through primary data and secondary data, then analyzed using qualitative analysis. The results of this research show that village origin rights are viewed from a juridical perspective in Law No. 6 of 2014 concerning villages and several further regulations related to villages provide recognition of guaranteeing village origin rights in a complex manner, village conflicts arise due to the role of the implementer of guaranteeing village origin rights. which is not optimal. Reviewing the legal regulations regarding villages, regional governments as implementers of the role of guaranteeing rights of origin must be more active through enacting regional regulations. The government is obliged to prioritize dialogue in resolving village conflicts and providing adequate compensation for village community land which is the object of national development. The issuance of Law No. 6 of 2014 concerning Villages, emphasizes the fulfillment of guarantees for village government administration based on rights of origin, which is then further regulated in the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration No. 1 of 2015 concerning Guidelines for Authority Based on Rights of Origin and Authority. The Village-Scale Local which is the benchmark for guidelines for procedures for implementing the authority of rights of origin is quite clear, as well as the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 18 of 2018 concerning Village Community Institutions and Village Traditional Institutions to become a meeting point for village governments and village traditional institutions. Abstrak: Tujuan penulisan skripsi ini adalah menganalisa fonemana konflik desa ditinjau dari bentuk penjaminan hak asal usul tradisional masyarakat desa sejak dikeluarkannya undang-undang no 6 tahun 2014 tentang desa. Metode penelitian ini menggunakan penelitian normatif, Jenis dan sumber bahan hukum yang digunakan dalam penyusunan penelitian ini ialah bahan hukum primer berasal dari peraturan perundang-undangan, bahan hukum sekunder diperoleh dari pengumpulan data-data kepustakaan berupa literatur- literatur, karya ilmiah, jurnal, dokumentasi dari berbagai lembaga atau instansi yang terkait, bahan hukum tersier petunjuk terhadap bahan hukum primer dan sekunder berupa kamus ensiklopedia, bahan dari internet dan literatur ilmiah, dan data yang terkumpul melalui data primer dan data sekunder, kemudian di analisis dengan analisis kualitatif. Hasil Penelitian ini menunjukan bahwa hak asal usul desa ditinjau dari segi yuridis dalam undang-undang no 6 tahun 2014 tentang desa dan beberapa pengaturan lanjutan terkait desa memberikan pengakuan penjaminan hak asal usul desa secara kompleks, konflik desa timbul akibat peran pelaksana penjaminan hak asal usul desa yang tidak optimal. Meninjau pengaturan peraturan perundang-undangan mengenai desa, pemerintah daerah sebagai pelaksana peran jaminan hak asal usul harus lebih aktif melalui penetapan peraturan daerah. Pemerintah wajib mengedepakan dialog dalam mengatasi konflik desa dan memberikan ganti rugi yang layak terhadap lahan masyarakat desa yang menjadi objek pembangunan nasional. Dikeluarkannya Undang-Undang No 6 Tahun 2014 Tentang Desa, mempertegas pemenuhan penjaminanan penyelenggaraan pemerintah desa berdasarkan hak asal usul yang kemudian diatur lebih lanjut pada Peraturan Menteri Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi No 1 Tahun 2015 Tentang Pedoman Kewenangan Berdasarkan Hak Asal Usul Dan Kewenangan Lokal Berskala Desa yang menjadi patokan pedoman tata cara dalam melaksanakan kewenangan hak asal usul cukup jelas, serta Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 18 Tahun 2018 Tentang Lembaga Kemasyarakatan Desa dan Lembaga Adat Desa untuk menjadi titik temu pemerintah desa dan lembaga adat desa.